FEATURES OF ADAPTIVE EXTENDED KALMAN FILTER IMPLEMENTATIONS - P. A. Khmarski; A. S. Solonar (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Features of adaptive extended Kalman filter implementations are considered. Recommendations about practical application of adaptive extended Kalman filter modifications are listed.